More and Better Food: An Egyptian Demonstration Project - National Research Council (The National Academies Press, 1986)
The More and Better Food Demonstration Project in Egypt is the product of multidisciplinary and multi-institutional collaboration among many Egyptian workers and institutions, with the National Research Centre (NRC) taking the leadership role. The ultimate goal of the project was to demonstrate the impact of science and technology on food, agriculture, and nutrition. The project was a major component of the Applied Science and Technology Research Program, a collaborative activity in science and technology for development supported by the Government of Egypt and the United States Agency for International Development during the years 1977-1986. More and Better Food: An Egyptian Demonstration Project is a case study of agricultural, nutrition, and health interventions in three Egyptian villages; it was written to inform an interested audience of development specialists, administrators, and others concerned with the role of science and technology in socioeconomic development. This report documents the integrated effort of more than 400 scientists concerned with the problems of food and nutrition. It is a case study of a research institute (NRC) that has adapted its system and mobilized its manpower to address a major development problem. More and Better Food focuses on aspects of planning, priority selection, management, and program impacts, as well as lessons learned.
Keywords: Food and Nutrition

Drinking Water and Health,: Volume 1 - National Research Council (The National Academies Press, 1977)
Keywords: Food and Nutrition